The Power of the Leadership of the Hukum Tua in the Administration of Village Government in Minahasa - Welly Waworundeng; Stefanus Sampe; Alfon Kimbal; Irfandi Pratama; Amanda F. Kaunang; Vebrian G. M. Bujung; Brandon C. D. Mamuaja (Univiversitas Dr. Djar Wattiheluw, 2025)
The Hukum Tua, or Village Head in North Sulawesi, holds unique authority and power compared to other village leaders. However, this authority and power have not been fully understood or optimally utilized. This study aims to identify the types of power exercised by the Hukum Tua in leading the administration of village government and society. A qualitative method was employed, with informants drawn from various village stakeholders. Data collection techniques included observation, interviews, literature review, and focus group discussions. The findings reveal that the Hukum Tua possesses both positional and personal power, though these have not been maximized in the leadership of village governance. The results also indicate that regulatory innovations have shifted and, in some cases, weakened the customary authority of the Hukum Tua, leading toward more democratic arrangements. These findings imply that the leadership of the Hukum Tua can be strengthened by harmonizing formal law and customary law to optimize the implementation of village governance.